PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, SISTEM PELAPORAN, DAN PARTISIPASI MASYARAKAT TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Ida Bagus Agung Yuda Andika; Ni Wayan Alit Erlina Wati (UNHI Press, 2021)
Village funds are funds used to fund governance, implementation of development, community development, and community empowerment. The purpose of this study was to examine the effect of the use of information technology, reporting systems, and community participation on the accountability of village fund management in villages in Kerambitan District. The population used in this study were all village officials in 15 villages in Kerambitan District, totaling 235 personnel. Determination of the sample using purposive sampling method in order to get 120 people as the sample. After the instrument test and classical assumption test were carried out, data analysis was carried out using multiple linear regression analysis, determination, t test, and F test. The results of the analysis showed that the use of information technology had a positive effect on the accountability of village fund management in villages in Kerambitan District. The reporting system has a positive effect on the accountability of village fund management in villages in Kerambitan District. Community participation has a positive effect on the accountability of village fund management in villages in Kerambitan District.